Development of Universe-Themed Augmented Reality-Based Flash Card Media for Children Aged 5-6 Years at Ananda Kindergarten Palembang - Anisa, Izzatil Anisa; Fahmi, Fahmi Fahmi; Dewi, Kurnia Dewi Kurnia (PIAUD Universitas Islam Negeri Sunan Kudus, 2023)
This study entitled Development of Augmented Reality-based Flash Card Media with the Theme of the Universe for children aged 5-6 years at Ananda Palembang Kindergarten aims to develop learning media by utilizing Augmented Reality-based technology. This Augmented Reality-based flash card media is the development of 3-dimensional (3D) card media. The research method used is Research and Development (R&D) with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The results showed that Flash Card Media based on Augmented Reality was developed based on the results of the material expert's assessment, namely 94.2 which was declared very valid, the results of the language expert's assessment, namely 84, which were stated to be very valid, the results of the assessment of media experts I, namely 90, which were stated to be very valid, the results of the assessment of media experts II, namely 96 was declared very valid, the results of the small-scale trial obtained a result of 95.2, which was decl3ared very good, and the large-scale trial obtained a result of 96.5. It was concluded that flash cards based on Augmented Reality were very suitable for use in learning media.Penelitian yang berjudul Pengembangan Media Flash Card Berbasis Augmented Reality Bertema Alam Semesta untuk Anak Usia 5-6 Tahun di TK Ananda Palembang ini bertujuan untuk mengembangkan media pembelajaran dengan memanfaatkan teknologi berbasis Augmented Reality. Media kartu flash berbasis Augmented Reality ini merupakan pengembangan dari media kartu 3 dimensi (3D). Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model penelitian ADDIE (Analysis, Design, Development, Implementation, Evaluation). Hasil penelitian menunjukkan Media Flash Card berbasis Augmented Reality dikembangkan berdasarkan hasil penilaian ahli materi yaitu 94,2 dinyatakan sangat valid, hasil penilaian ahli bahasa yaitu 84 dinyatakan sangat valid, hasil penilaian ahli media I yaitu 90 dinyatakan sangat valid, hasil penilaian ahli media II yaitu 96 dinyatakan sangat valid, hasil uji coba skala kecil diperoleh hasil 95,2 dinyatakan sangat baik, dan uji coba skala besar memperoleh hasil sebesar 96,5. Disimpulkan bahwa flash card berbasis Augmented Reality sangat layak digunakan dalam media pembelajaran.